Visualization of calcium channel blockers in human adrenal tissues and their possible effects on steroidogenesis in the patients with primary aldosteronism (PA). Issue 218 (April 2022) - Motomura, Naoki; Yamazaki, Yuto; Gao, Xin; Tezuka, Yuta; Omata, Kei; Ono, Yoshikiyo; Morimoto, Ryo; Satoh, Fumitoshi; Nakamura, Yasuhiro; Shim, Jaeyoon; Choi, Man Ho; Ito, Akihiro; et al.
Highlights: Intra-adrenal amlodipine visualization using MALDI-MSI was firstly accomplished. Intra-adrenal amlodipine accumulation was more pronounced than in peri-adrenal adipose tissues. HSD3B activity in APAs was suppressed in amlodipine treated patients. Amlodipine could possibly exert its effects on steroidogenesis mainly via CaV1.2. Abstract: Voltage-gated L-type calcium channel (CaV) isoforms are well known to play pivotal tissue-specific roles not only in vasoconstriction but also in adrenocortical steroidogenesis including aldosterone biosynthesis. Alpha-1C subunit calcium channel (CC) (CaV1.2) is the specific target of anti-hypertensive CC blockers (CCBs) and its Alpha-1D subunit (CaV1.3) regulates depolarization of cell membrane in aldosterone-producing cells. Direct effects of CCBs on aldosterone biosynthesis were previously postulated but their intra-adrenal distribution and effects on steroid production in primary aldosteronism (PA) patients have remained virtually unknown. In this study, frozen tissue specimens constituting tumor, adjacent adrenal gland and peri-adrenal adipose tissues of nine aldosterone-producing adenoma (APA) cases were examined for visualization of amlodipine and aldosterone themselves using matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI). Liquid chromatography-mass spectrometry (LC–MS) analysis was also performed to quantify amlodipine and 17 adrenal steroids in those cases above and compared the findings with immunohistochemical analysis of steroidogenic enzymes and calcium channels (CaV1.2 and CaV1.3). Effects of amlodipine on mRNA level of aldosterone biosynthetic enzymes were also explored using human adrenocortical carcinoma cell line (H295R). Amlodipine-specific peak ( m/z 407.1 > 318.1) was detected only in amlodipine treated cases. Accumulation of amlodipine was marked in adrenal cortex compared to peri-adrenal adipose tissues but not significantly different between APA tumors and adjacent adrenal glands, which was subsequently confirmed by LC–MS quantification. Intra-adrenal distribution of amlodipine was generally consistent with that of CCs. In addition, quantitative steroid profiles using LC–MS and in vitro study demonstrated the lower HSD3B activities in amlodipine treated cases. Immunoreactivity of CaV1.2 and HSD3B2 were also correlated. We report the first demonstration of specific visualization of amlodipine in human adrenal tissues by MALDI-MSI. Marked amlodipine accumulation in the adrenal glands suggested its direct effects on steroidogenesis in PA patients, possibly targeting on CaV1.2 and suppressing HSD3B activity.